KELAYAKAN USAHATANI SEMANGKA (Citrullus lanatus) DI KECAMATAN NGOMBOL, KABUPATEN PURWOREJO - Heri Dres Hermanto; Ignatius Suprih Sudrajat; Ari Astuti (JURNAL ILMIAH AGRITAS, 2019)
Â Â  The purpose of the research is to analyze the feasibility of watermelon farming in Wonosari Village, Ngombol District, Purworejo Regency and find out the factors that influence the success of watermelon farming. It was assumed that the farmers, land, capital, labor, technology, extension facilities, production and prices affected the success of watermelon farming in Wonosari Village. The method of determining the research area was carried out purposively while the sampling method used simple random sampling with 33 watermelon farmers as respondents. The feasibility analysis using the t test and multiple linear regression analysis.The revenue of each farm (0,42 ha) is Rp. 11,360,606.06 and the average total cost is about Rp. 4854,422.81 per 0.42 ha. The average income of watermelon farming is about Rp. 11,506,183.25 per 0.42 ha. Watermelon farming is feasible to be cultivated with the result of R / C Ratio is 3.37. The factors that influence the success of watermelon farming with multiple linear regression using T-test show that the variables of farmer (x1) and land area (x2) has no significant effect on success. While variables of capital (x3), labor (x4), technology (x5), extension facilities (x6), price (x7), and production (x8) have a significant effect on the success of watermelon farming. The F-count test from the test results obtained a value of sig 0,000 smaller than 0.05 and F-count is 18.584 greater than F-table 2.034 which means Ha is accepted, also means there is an influence of variables simultaneously on y.